Media Pembelajaran Ruang Guru Berbasis Teknologi Sebagai Inovasi Pembelajaran Era Revolusi Industri 4.0 - Dwi Amanda; Kenanga Safitri; Veri Ferdiansyah; Nurbaiti Nurbaiti (Ebisnis Manajemen, 2023)
The Industrial Revolution 4.0 has substantially changed human life, work and social interactions. The learning process experiences many innovations along with very fast digital developments and technological advances. At the beginning of the industrial revolution 4.0 there were many new innovations, especially in the education sector, one of which was the Ruangguru application. The progress of the country depends on good education. This research uses a qualitative approach and library research as methods, with researchers as the main tool. The data collection method is qualitative, and data analysis is inductive. Problems are discovered and explained through research. At first, the researcher only understood the problem in general, after that, the researcher concluded more specifically. By using the literature review method, the researcher diligently examined the required documents. The existence of "Ruangguru" changes the teacher's work to be more productive and positive.